Answer:
x = 4
Step-by-step explanation:
9(x - 2) = 18
9x - 18 = 18
9x = 18 + 18
9x = 36
x = 36/9
x = 4
Answer:
a?
Step-by-step explanation:
Answer:
(x - 9)(x + 3)
Step-by-step explanation:
Given
x² - 6x - 27
Consider the factors of the constant term (- 27) which sum to give the coefficient of the x- term (- 6)
The factors are - 9 and + 3, since
- 9 × 3 = - 27 and - 9 + 3 = - 6, thus
x² - 6x - 27 = (x - 9)(x + 3)
A = b*h*0.5
24 = 4*0.5*h
24 = 2*h
h = 12
Height is 12 inches.
#3.) 48 pieces of ribbon
#3.) this week they cost $112